Operational interactions between sea lion species (Otariinae) and commercial fisheries - Ramos, Karina; Machado, Rodrigo; Schiavetti, Alexandre (Ethnobiology and Conservation, 2020)
Many marine mammal species, such as pinnipeds, have shown an increased frequency of interaction with fisheries. Thus, we aimed to investigate the operational interactions between commercial fishing and sea lion species of all five continents, between 1982 and 2018. We found 130 publications in which operational interactions between commercial fisheries and the species of sea lions were detected, in 12 countries. These interactions included bycatch, presence of the animals around boats, depredation, gear damage, entanglement in lost/discarded fishing gear, boat collisions, aggressions, gear-related injuries and harassment. Trawl and gillnet fisheries showed significantly increased association with bycatch, although purse seine fishing was reported as having the largest groups of pinnipeds in the interactions. Gillnet and line fisheries registered more events of depredation and gear damage. Other interactions, such as entanglement and aggressions, were also very common for all species. We suggest that the interactions should be monitored using the data of onboard observers from different fleets and fisheries. Bycatch limits, change in fishing practices, decreased fishing effort, and the establishment of effective MPAs may reduce impact on the fauna. Moreover, data on bycatch should be standardized to enable comparisons between fisheries and locations. The extent of commercial losses caused by pinnipeds should also be characterized to depict the real impact of operational interactions in fisheries economy. Lastly, the identification of interaction hotspots can enable efficient conflict management in the affected areas.